Population study of long-tailed macaque (Macaca fascicularis) on Deli Island, Banten, Indonesia - YULI S. FITRIANA; EKO SULISTYADI; RIZKI KURNIA TOHIR; MHD MUHAJIR HASIBUAN; FARID RIFAIE; IBNU MARYANTO; ARIE MULIA LUBIS; M. FAJRUR RIFQI (Society for Indonesian Biodiversity, 2024)
Abstract. Fitriana YS, Sulistyadi E, Tohir RK, Hasibuan MM, Rifaie F, Maryanto I, Lubis AM, Rifqi MF. 2024. Population study of long-tailed macaque (Macaca fascicularis) on Deli Island, Banten, Indonesia. Biodiversitas 25: 144-150. Understanding the distribution and population dynamics of primate species is essential for practical conservation efforts. However, such information is often unavailable, even for species whose populations appear abundant. The long-tailed macaque (Macaca fascicularis Raffles, 1821) is a species with a wide range in Southeast Asia, including Sumatra, Java, Kalimantan, Bali, Lombok, and Lesser Sunda in Indonesia. However, comprehensive data on population density across its Indonesian distribution area still needs to be improved. To address this knowledge gap, we conducted a thorough survey and study to estimate the population density of long-tailed macaques on Deli Island, located in Banten Province. Long-tailed macaques were introduced to Deli Island between 1989 and 1990 with a total of 1000 males and 10,000 females. To date, a total of 9,500 individuals have been harvested from this island in the period 1991-2010. We employed the line transect distance sampling (LTDS) method with a perpendicular distance approach that covered all habitat types throughout the island. Our findings revealed that the population density of long-tailed macaques on Deli Island is approximately five individuals per hectare, with an estimated total population of 4,860. The data pertaining to age structure and sex ratio is notably limited, primarily due to challenges in identification caused by dense vegetation. To address these limitations and acquire a more comprehensive understanding, additional research is essential for the accurate determination of the age structure and sex ratio on the island. Our study provides crucial baseline data for conserving this species. We recommend implementing a systematic survey encompassing the entire distribution range of the long-tailed macaque across Indonesia. Such an initiative will be instrumental in assessing its threat status and laying out a comprehensive plan for conservation efforts.